2021
DOI: 10.1002/hyp.14040
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus retention in constructed wetlands enhanced by zeolite‐ and clinopyroxene‐dominated lava sand

Abstract: Constructed wetlands (CWs) are engineered systems for treating wastewater by sequestering nutrients and contaminants. Our aim was to assess the main phosphorus (P) binding states in operating CWs to assess P saturation and indications on P recycling potential of filter materials, which might be necessary under future peak P scenarios. The investigated vertical flow CWs (operation time up to 16 years) are based on either fluviatile (Fluv) sand or zeolite-(Ze-LS) and clinopyroxene (Cl-LS)dominated lava sand. Org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
(126 reference statements)
1
3
0
Order By: Relevance
“…Elimination rates for P tot load varied from 83.4% in Phase 2, 56.8% in Phase 4b to 18.4% in Phase 5c (see Table 1). In contrast, the lava sand compartment exhibited P tot effluent values <0.05 mg/L (LOD) at all times (P elimination rates >97%), which corroborates literature findings of enhanced phosphorus removal in zeolite-containing lava sand CW that treat municipal wastewater from combined sewer systems in Germany, even after operating times of years [30,33]. P removal is improved by the high natural zeolite content of lava sands [33] and the increased contact time between VFCW and porous media in the filter [30].…”
Section: Phosphorus Retentionsupporting
confidence: 88%
“…Elimination rates for P tot load varied from 83.4% in Phase 2, 56.8% in Phase 4b to 18.4% in Phase 5c (see Table 1). In contrast, the lava sand compartment exhibited P tot effluent values <0.05 mg/L (LOD) at all times (P elimination rates >97%), which corroborates literature findings of enhanced phosphorus removal in zeolite-containing lava sand CW that treat municipal wastewater from combined sewer systems in Germany, even after operating times of years [30,33]. P removal is improved by the high natural zeolite content of lava sands [33] and the increased contact time between VFCW and porous media in the filter [30].…”
Section: Phosphorus Retentionsupporting
confidence: 88%
“…Interestingly, Alewell et al. (2021) reported the accumulation of complex phosphomonoesters in constructed (non‐soil) wetlands after 16 yr of operation, which suggests that microbial turnover of organic material may be an important factor in their synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies on soil Po have already found an association with complex phosphomonoesters and that of soil organic C, which appear to accumulate on a decadal timeframe (McLaren et al, 2017;McLaren, Smernik, McLaughlin, McBeath, et al, 2020;Schefe et al, 2015). Interestingly, Alewell et al (2021) reported the accumulation of complex phosphomonoesters in constructed (non-soil) wetlands after 16 yr of operation, which suggests that microbial turnover of organic material may be an important factor in their synthesis.…”
Section: Implications For the Composition Of Soil Pomentioning
confidence: 98%
“…One focus of her research is on the development of indicators for wetland degradation and regeneration. In their paper,Alewell et al (2021), they assessed the main phosphorus binding states in operating constructed wetlands to assess phosphorus saturation and indications on phosphorus recycling potential of filter materials. They showed that phosphorus accumulation increased with age of the investigated vertical flow constructed wetlands in all three investigated filter materials (fluviatile sands, zeolite-and clinopyroxene-dominated lava sands) and most of the phosphorus was accumulated in the upper horizons.Dr.…”
mentioning
confidence: 99%